Fe-BTC coated aluminum sludge based phosphorus removal adsorbent and preparation method thereof

By heat treatment and acid activation of aluminum sludge, combined with organic ligands and FeCl3·6H2O, Fe-BTC-coated aluminum sludge-based phosphorus removal adsorbent was prepared, solving the problems of low and unstable adsorption capacity of aluminum sludge. It achieved efficient and stable phosphate adsorption and low metal leaching, making it suitable for large-scale production.

CN119258991APending Publication Date: 2025-01-07CHANGAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411528454.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing aluminum sludge adsorbents have low and unstable adsorption capacity and high metal leaching rate, making them difficult to effectively treat eutrophication problems in water bodies.

Method used

Fe-BTC-coated aluminum sludge-based phosphorus removal adsorbent was prepared by heat treatment and acid activation of aluminum sludge, combined with organic ligands and FeCl3·6H2O, thereby improving its specific surface area and chemical stability.

Benefits of technology

It enhances the adsorption capacity for phosphates, reduces the metal leaching rate, achieves efficient and stable phosphorus removal, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258991A_ABST
    Figure CN119258991A_ABST
Patent Text Reader

Abstract

The invention relates to a Fe-BTC coated aluminum sludge based phosphorus removal adsorbent and a preparation method thereof. On the basis of heat treatment and acid activation of aluminum sludge, high-porosity Fe-BTC is further coated on the surface of the aluminum sludge by using an organic ligand and FeCl3. 6H2O, so that the phosphorus removal adsorbent is obtained. According to the method, Fe-BTC is adopted to coat the aluminum sludge subjected to heat treatment and acid activation treatment, so that the specific surface area of the adsorbent is effectively increased, meanwhile, the structure of the composite adsorbent is stabilized, the metal dissolution rate is reduced, and waste resource utilization is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental protection, and in particular to a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent and a preparation method thereof. Background Art

[0002] Phosphorus is one of the most critical factors leading to eutrophication of water bodies. Excessive discharge of phosphorus-containing wastewater will continue to expand the speed and scope of eutrophication of water bodies and damage the aquatic ecosystem. Therefore, phosphorus removal is a key measure to solve the problem of eutrophication of water bodies.

[0003] At present, there are mainly biological, chemical and physical methods. Biological and chemical methods are mature in technology, but the treatment cost is high, the amount of sludge produced is large, and it is easy to cause secondary pollution. The adsorption method is gradually being widely used because of its simple operation and low cost.

[0004] Aluminum sludge is a by-product of the water purification process in a water plant. 3 The sewage treatment plants produce an average of 10 tons of aluminum sludge every day. The output of aluminum sludge is huge and the treatment cost is expensive. However, due to the good adsorption capacity of anions by the rich hydrated aluminum oxides in aluminum sludge, it has become a resource with great development potential in the field of water treatment adsorption.

[0005] In the application process, the primary aluminum sludge has the problem of low adsorption capacity, so it is necessary to modify the primary aluminum sludge to increase its adsorption capacity. Existing technologies such as heat treatment, acid activation, and preparation of aluminum sludge hydrogel microspheres have adjusted the material morphology, electronic structure and surface chemical properties to a certain extent, improved the adsorption performance, and increased the adsorption capacity, but the prepared materials are still unstable and the metal dissolution rate is high, and the adsorption effect is still not ideal.

[0006] Therefore, further research is needed on how to modify aluminum sludge to improve its comprehensive utilization effect. Summary of the invention

[0007] The purpose of the present invention is to overcome the above technical problems and provide a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent with good chemical stability and adsorption efficiency.

[0008] Another object of the present invention is to provide a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent.

[0009] Another object of the present invention is to provide an Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent for use in treating the eutrophication problem of water resources.

[0010] In order to achieve the above object, the present invention provides a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which is prepared by the following steps:

[0011] 1) firstly heat-treating the original aluminum sludge without any treatment, and then cooling it to room temperature to obtain the heat-treated aluminum sludge;

[0012] 2) then subjecting the heat-treated aluminum sludge to acid activation treatment with an inorganic acid solution, washing to neutrality after the treatment, and drying to obtain a heat-treated acid-activated aluminum sludge-based material;

[0013] 3) mixing the organic ligand and the inorganic base solution evenly and setting the mixture as solution 1 for later use;

[0014] 4) FeCl 3 6H 2 O and the heat-treated acid-activated aluminum sludge-based material obtained in step 2) are mixed uniformly in water as solution 2 for standby use;

[0015] 5) adding the solution 2 prepared in step 4) dropwise into the solution 1 prepared in step 3) at room temperature, and continuously stirring, collecting the precipitate, washing and drying it to obtain a dephosphorus adsorbent.

[0016] Wherein, the heat treatment temperature in step 1) is 300-800° C., and the heat treatment time is 0.5-4 h.

[0017] The weight-to-volume ratio of the heat-treated aluminum sludge to the inorganic acid solution in step 2) is 1:1-6 (g / ml).

[0018] The inorganic acid solution is a hydrochloric acid solution or a sulfuric acid solution. The concentration of the hydrochloric acid solution is 0.5-6 mol / L, and the concentration of the sulfuric acid solution is 0.5-3 mol / L.

[0019] The acidification treatment is carried out at room temperature and pressure, and stirring can be performed at 300-500 rpm for 2-4 hours.

[0020] The washing can be carried out using deionized water.

[0021] The molar ratio of the organic ligand to the inorganic base solution in step 3) is 1:2-4.

[0022] The organic ligand is trimesic acid, terephthalic acid, isophthalic acid or biphenyl dicarboxylic acid; the inorganic alkali solution can be sodium hydroxide solution, potassium hydroxide solution or the like.

[0023] Step 4) FeCl 3 6H 2 The weight ratio of O to the heat-treated acid-activated aluminum sludge-based material is 1:0.2~1.

[0024] In step 5), the amount of solution 1 and solution 2 is based on the ratio of the organic ligand to FeCl 3 6H 2The molar ratio of O is 1:1~2.

[0025] The washing is carried out using water and anhydrous ethanol, preferably three times of alternating washing with water and anhydrous ethanol, respectively, to effectively remove unreacted precursor raw materials.

[0026] The continuous stirring speed is 300-500 rpm, and the stirring time is 1-24 hours.

[0027] The present invention also provides a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, comprising the following steps:

[0028] 1) firstly heat-treating the original aluminum sludge without any treatment, and then cooling it to room temperature to obtain the heat-treated aluminum sludge;

[0029] 2) then subjecting the heat-treated aluminum sludge to acid activation treatment with an inorganic acid solution, washing to neutrality after the treatment, and drying to obtain a heat-treated acid-activated aluminum sludge-based material;

[0030] 3) mixing the organic ligand and the inorganic base solution evenly and setting the mixture as solution 1 for later use;

[0031] 4) FeCl 3 6H 2 O and the heat-treated acid-activated aluminum sludge-based material obtained in step 2) are mixed uniformly in water as solution 2 for standby use;

[0032] 5) adding the solution 2 prepared in step 4) dropwise into the solution 1 prepared in step 3) at room temperature, and continuously stirring, collecting the precipitate, washing and drying it to obtain a dephosphorus adsorbent.

[0033] Preferably, the heat treatment temperature in step 1 is 300-800° C., and the heat treatment time is 0.5-4 h.

[0034] The weight-to-volume ratio of the heat-treated aluminum sludge to the inorganic acid solution in step 2) is 1:1-6 (g / ml).

[0035] The inorganic acid solution is a hydrochloric acid solution or a sulfuric acid solution. The concentration of the hydrochloric acid solution is 0.5-6 mol / L, and the concentration of the sulfuric acid solution is 0.5-3 mol / L.

[0036] The acidification treatment is carried out at room temperature and pressure, and stirring can be performed at 300-500 rpm for 2-4 hours.

[0037] The washing can be carried out using deionized water.

[0038] The molar ratio of the organic ligand to the inorganic base solution in step 3) is 1:2-4.

[0039] The organic ligand is trimesic acid, terephthalic acid, isophthalic acid or biphenyl dicarboxylic acid, preferably trimesic acid; the inorganic alkali solution can be sodium hydroxide solution, potassium hydroxide solution or the like.

[0040] Step 4) FeCl 3 6H 2 The weight ratio of O to the heat-treated acid-activated aluminum sludge-based material is 1:0.2~1.

[0041] In step 5), the amount of solution 1 and solution 2 is based on the ratio of the organic ligand to FeCl 3 6H 2 The molar ratio of O is 1:1~2.

[0042] The washing is carried out using water and anhydrous ethanol, preferably three times of alternating washing with water and anhydrous ethanol, respectively, to effectively remove unreacted precursor raw materials.

[0043] The continuous stirring speed is 300-500 rpm, and the stirring time is 1-24 hours.

[0044] The Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent of the present invention is used for treating the eutrophication problem of water bodies in water resources.

[0045] The Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent of the present invention generates a high-porosity Fe-BTC material on its surface based on heat treatment and acid activation of aluminum sludge. The phosphorus removal adsorbent of the present invention not only increases the specific surface area and adsorption sites of the adsorbent, but also increases the phosphate adsorption amount. It has the following outstanding advantages and effects:

[0046] 1. The present invention modifies aluminum sludge by combining heat treatment and acid activation, effectively increasing its specific surface area and the number of surface active sites, and enhancing its adsorption capacity for phosphate.

[0047] 2. The present invention utilizes an organic ligand (preferably trimesic acid) and FeCl 3 6H 2 The porous MOFs material of Fe-BTC was grown on the surface of the heat-treated acid-activated aluminum sludge-based material to achieve the coating of the aluminum sludge material, further increase the specific surface area of ​​the adsorbent, optimize the structure of the composite adsorbent, and make it have higher chemical stability and adsorption efficiency.

[0048] 3. In addition, Fe-BTC can be directly synthesized using iron salts and organic ligands at room temperature and pressure without the need for special synthesis conditions and further post-processing. The preparation process is simple to operate, with mild conditions, without the need for complex equipment, and has low cost, making it suitable for large-scale production applications.

[0049] 4. The phosphorus removal adsorbent of the present invention can still maintain a high adsorption effect after repeated use, and the metal dissolution rate is low, thus avoiding the problem of secondary pollution and showing good environmental friendliness and sustainability.

[0050] 5. The method proposed in the present invention makes full use of aluminum sludge, a by-product of water plants, which not only realizes the resource utilization of waste, but also provides a new idea for solving the problem of eutrophication of water bodies, realizes the strategy of "treating waste with waste and turning waste into treasure", and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1a This is a SEM image of the phosphorus removal adsorbent prepared in Comparative Example 1, with a resolution of 1 μm;

[0052] Figure 1b , 1c They are respectively SEM images of the phosphorus removal adsorbent prepared in Example 1 of the present invention, wherein: Figure 1b The resolution is 1μm. Figure 1c The resolution is 500nm;

[0053] Figure 1d This is the EDS image of the phosphorus removal adsorbent prepared in Example 1 of the present invention;

[0054] Figure 2 The XRD diagrams of the phosphorus removal adsorbent and pure Fe-BTC prepared in Example 1 and Comparative Example 1 of the present invention;

[0055] Figure 3 (a) N2 adsorption-desorption isotherms and (b) pore size distribution of the phosphorus removal adsorbents prepared in Example 1 of the present invention and Comparative Example 1;

[0056] Figure 4 The pseudo-first-order kinetic and pseudo-second-order kinetic models of the phosphorus removal adsorbent prepared in Example 1 of the present invention are fitted;

[0057] Figure 5 The fitting of the pseudo-first-order kinetic and pseudo-second-order kinetic models of the phosphorus removal adsorbent prepared in Comparative Example 1;

[0058] Figure 6 This is a graph showing the adsorption amount of the phosphorus removal adsorbent prepared in Example 1 of the present invention during 5 adsorption regeneration cycles. DETAILED DESCRIPTION

[0059] Embodiments of the present invention are described below with reference to the accompanying drawings. Elements and features described in one drawing or one embodiment of the present invention may be combined with elements and features shown in one or more other drawings or embodiments. It should be noted that for the purpose of clarity, the representation and description of components or processes that are not related to the present invention and are known to those of ordinary skill in the art are omitted in the drawings and descriptions.

[0060] The present invention is further described below in conjunction with the accompanying drawings.

[0061] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples and comparative examples are purchased from commercial channels unless otherwise specified.

[0062] Example 1

[0063] This embodiment proposes a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which specifically includes the following steps:

[0064] S1. Take the original aluminum sludge without any treatment, put it into a porcelain boat, place it in a tube furnace, heat it to 600°C, keep it for 1 hour, and cool it to room temperature to obtain heat-treated aluminum sludge;

[0065] S2, the heat-treated aluminum sludge prepared in step S1 is mixed evenly, 5.0 g is added to 5 mL of a 2.0 mol / L hydrochloric acid solution, and stirred at 300 rpm for 2 h under normal pressure, and then washed with deionized water to neutrality after drying, and dried again to obtain a heat-treated acid-activated aluminum sludge-based material;

[0066] S3, adding 0.263 g of trimesic acid to 10 mL of aqueous solution containing 0.15 g of NaOH, stirring and dissolving uniformly to obtain solution 1;

[0067] S4, 0.508g FeCl 3 6H 2 O and 0.3 g of the heat-treated acid-activated aluminum sludge-based material prepared in step S2 were added into 10 mL of water, stirred to dissolve and disperse uniformly, and a solution 2 was obtained;

[0068] S5. Under the condition of 300 rpm magnetic stirring, the solution 2 prepared in step S4 is added dropwise into the solution 1 prepared in step S3 to immediately produce a black-brown solid. The mixture is stirred continuously at 300 rpm for 6 h at room temperature. The precipitate is collected by centrifugation. The precipitate is washed alternately with water and anhydrous ethanol three times, and finally placed in an oven to dry to obtain a dephosphorus adsorbent.

[0069] Example 2

[0070] This embodiment provides a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which specifically includes the following steps:

[0071] S1. Take the original aluminum sludge without any treatment, put it into a porcelain boat, place it in a tube furnace and heat it to 800°C, keep it for 0.5h, and cool it to room temperature to obtain heat-treated aluminum sludge;

[0072] S2, the heat-treated aluminum sludge prepared in step S1 is mixed evenly, 5.0 g is added into 10 mL of 6 mol / L hydrochloric acid solution, and stirred at 300 rpm for 2 h under normal pressure, and then washed with deionized water to neutrality after drying, and dried again to obtain a heat-treated acid-activated aluminum sludge-based material;

[0073] S3, adding 0.263 g of isophthalic acid to 10 mL of an aqueous solution containing 0.15 g of KOH, stirring and dissolving uniformly to obtain a solution 1;

[0074] S4, 0.508g FeCl 3 6H 2 O and 0.1 g of the heat-treated acid-activated aluminum sludge-based material prepared in step S2 were added into 10 mL of water, stirred to dissolve and disperse uniformly, and a solution 2 was obtained;

[0075] S5. Under the condition of 300 rpm magnetic stirring, add solution 2 prepared in step S4 dropwise into solution 1 prepared in step S3 to immediately produce a dark brown solid. Stir continuously at 300 rpm at room temperature for 1 hour, collect the precipitate by centrifugation, wash the precipitate three times alternately with water and anhydrous ethanol, and finally place it in an oven to dry to obtain a dephosphorus adsorbent.

[0076] Example 3

[0077] This embodiment proposes a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which specifically includes the following steps:

[0078] S1. Take the original aluminum sludge without any treatment, put it into a porcelain boat, place it in a tube furnace, heat it to 300°C, keep it for 4 hours, and cool it to room temperature to obtain heat-treated aluminum sludge;

[0079] S2, the heat-treated aluminum sludge prepared in step S1 is mixed evenly, 5.0 g is added into 30 mL of 1.0 mol / L sulfuric acid solution, and stirred at 300 rpm for 2 h under normal pressure, and then washed with deionized water to neutrality after drying, and dried again to obtain a heat-treated acid-activated aluminum sludge-based material;

[0080] S3, adding 0.263 g of terephthalic acid to 10 mL of aqueous solution containing 0.15 g of NaOH, stirring and dissolving uniformly to obtain solution 1;

[0081] S4, 0.508g FeCl 3 6H 2 O and 0.5 g of the heat-treated acid-activated aluminum sludge-based material prepared in step S2 were added into 10 mL of water, stirred to dissolve and disperse uniformly, to obtain solution 2;

[0082] S5. Under the condition of 300 rpm magnetic stirring, the solution 2 prepared in step S4 is added dropwise into the solution 1 prepared in step S3 to immediately produce a black-brown solid. The mixture is stirred continuously at 300 rpm for 24 h at room temperature. The precipitate is collected by centrifugation and washed alternately with water and anhydrous ethanol three times. Finally, the precipitate is dried in an oven to obtain a dephosphorus adsorbent.

[0083] Example 4

[0084] This embodiment proposes a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which specifically includes the following steps:

[0085] S1. Take the original aluminum sludge without any treatment, put it into a porcelain boat, place it in a tube furnace, heat it to 300°C, keep it for 4 hours, and cool it to room temperature to obtain heat-treated aluminum sludge;

[0086] S2, the heat-treated aluminum sludge prepared in step S1 is mixed evenly, 5.0 g is added into 30 mL of 1.0 mol / L hydrochloric acid solution, and stirred at 500 rpm for 4 h under normal pressure, and then washed with deionized water to neutrality after drying, and dried again to obtain a heat-treated acid-activated aluminum sludge-based material;

[0087] S3, adding 0.263 g of biphenyl dicarboxylic acid to 10 mL of aqueous solution containing 0.15 g of NaOH, stirring and dissolving uniformly to obtain solution 1;

[0088] S4, 0.508g FeCl 3 6H 2 O and 0.4 g of the heat-treated acid-activated aluminum sludge-based material prepared in step S2 were added into 10 mL of water, stirred to dissolve and disperse uniformly, and a solution 2 was obtained;

[0089] S5. Under the condition of 300 rpm magnetic stirring, the solution 2 prepared in step S4 is added dropwise into the solution 1 prepared in step S3 to immediately produce a black-brown solid. The mixture is stirred at 300 rpm for 12 h at room temperature. The precipitate is collected by centrifugation. The precipitate is washed alternately with water and anhydrous ethanol three times, and finally dried in an oven to obtain a dephosphorus adsorbent.

[0090] Comparative Example 1

[0091] This comparative example proposes a method for preparing a Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, which differs from Example 1 in that Fe-BTC is not coated on the surface of the heat-treated acid-activated aluminum sludge-based material, and the remaining components, component contents, and experimental steps are the same as those in Example 1, specifically comprising the following steps:

[0092] S1. Take the original aluminum sludge without any treatment, put it into a porcelain boat, place it in a tube furnace, heat it to 600°C, keep it for 1 hour, and cool it to room temperature to obtain heat-treated aluminum sludge;

[0093] S2. Mix the heat-treated aluminum sludge prepared in step S1 evenly, take 5.0 g and add it to 5 mL of 2.0 mol / L hydrochloric acid solution, and stir it at 300 rpm for 2 hours under normal pressure. After drying, wash it with deionized water until it is neutral, and dry it again to obtain a dephosphorus adsorbent.

[0094] Experimental Example 1

[0095] The surface morphologies of the dephosphorization adsorbents prepared in Example 1 and Comparative Example 1 were observed by scanning electron microscopy (SEM), and the elemental composition of the dephosphorization adsorbent prepared in Example 1 was analyzed by EDS energy spectrum.

[0096] Figure 1a This is the SEM image of the phosphorus removal adsorbent prepared in Comparative Example 1. Figure 1b , Figure 1c They are respectively SEM images of the phosphorus removal adsorbent prepared in Example 1 of the present invention, Figure 1d This is the EDS spectrum of the dephosphorization adsorbent prepared in Example 1. As shown in the figure, compared with the dephosphorization adsorbent prepared in Comparative Example 1, the surface of the dephosphorization adsorbent prepared in Example 1 presents granular Fe-BTC wrapped in larger flat-layer particles, heat-treated acid-activated aluminum sludge-based materials, which are stacked together in a disordered manner to form clusters. It can be seen that the prepared Fe-BTC material is an aggregate of many small nanocrystals with a particle size between 50-80nm, indicating the successful preparation of the dephosphorization adsorbent. EDS spectrum analysis shows that the main elemental components of the dephosphorization adsorbent prepared in Example 1 are C, O, Si, Al, Fe and Cl. At the same time, it can also be inferred that the Fe-BTC particles have been loaded on the aluminum sludge, and the presence of Cl ions includes the Cl ions existing in the aluminum sludge itself and the NaCl formed during the preparation process dissolved in the solution.

[0097] Similarly, the elements of the dephosphorization adsorbent prepared in Example 2-4 were analyzed by scanning electron microscopy (EDS), and it can be seen that the main elements are C, O, Si, Al, Fe and Cl, indicating that the Fe-BTC particles have been loaded on the aluminum sludge.

[0098] Experimental Example 2

[0099] In this experimental example, X-ray diffraction was used to characterize and analyze the structural characteristics of the phosphorus removal adsorbent prepared in Example 1 and Comparative Example 1 and pure Fe-BTC.

[0100] Figure 2 The XRD patterns of the dephosphorization adsorbents prepared in Example 1 and Comparative Example 1 and pure Fe-BTC are shown in the figure. As shown in the figure, the adsorbent prepared in Example 1 has characteristic peaks at 2θ of 6.63°, 10.63°, and 18.62°, including the characteristic peaks of the adsorbent prepared in Comparative Example 1, and is basically consistent with the main peak of the XRD spectrum of pure Fe-BTC, indicating that the main mineral phase of the dephosphorization adsorbent also includes the main SiO 2 and Al 2 O 3 et al., and the successful synthesis of Fe-BTC crystals, while no Fe 2 O 3 Characteristic peaks of the phase.

[0101] Experimental Example 3

[0102] In this experimental example, the BET test was used to analyze the specific surface area and pore characteristics of the phosphorus removal adsorbents prepared in Example 1 and Comparative Example 1.

[0103] Table 1 Pore characteristics of phosphorus removal adsorbents

[0104]

[0105] Figure 3 The phosphorus removal adsorbent prepared in Example 1 and Comparative Example 1 (a) N 2 (a) adsorption-desorption isotherms and (b) pore size distribution; Table 1 shows the pore characteristics of the phosphorus removal adsorbents prepared in Example 1 and Comparative Example 1. Figure 3 As shown, the N of the phosphorus removal adsorbent prepared in Example 1 and Comparative Example 1 is 2 The adsorption-desorption isotherms are all type IV isotherms. The phosphorus removal adsorbent prepared in Example 1 is under a low partial pressure of 0.4-1.0, N 2 The adsorption-desorption isotherm showed a hysteresis loop which is common in mesoporous materials.

[0106] It can be seen from Table 1 that the surface area of ​​the dephosphorization adsorbent prepared in Example 1 (481.01 m 2 / g) and pore volume (0.41cm 3 / g), the specific surface area and pore volume are 5.7 times and 16.8 times that of comparative example 1, respectively, indicating that the composite material formed by particle stacking and coating has a larger surface area, which also means that there are more active sites for adsorption. The phosphorus removal adsorbent prepared in Example 1 has a narrow micropore distribution, most of which are located at 2.0-4.0nm, and the material has a high porosity.

[0107] Experimental Example 4

[0108] This experimental example aims to study the kinetics of phosphate adsorption.

[0109] The adsorption kinetics experiment was carried out in a centrifuge tube. 50 mg of the phosphorus removal adsorbent prepared in Example 1 and Comparative Example 1 were weighed and placed in 50 mL of a 50 mg / L phosphate solution. The adsorption process was carried out in an oscillating incubator at 25, 30, 35 and 40 ° C and 150 rpm. The kinetics was determined by collecting the phosphate concentrations at different contact times of 10, 30, 60, 120, 180, 300, 480, 720, 1080, 1440, 1800 and 2160 min. After sampling, the sample was filtered with a 0.22 μm filter head, and the residual concentration of phosphate at time t was determined by using an ultraviolet spectrophotometer at 700 nm. The adsorption capacity at time t was calculated as Qt = [(initial phosphate concentration-phosphate concentration at time t) / adsorbent mass] / total volume of the solution. The phosphate adsorption kinetics were studied using pseudo-first-order kinetics and second-order kinetics fitting, and the theoretical adsorption amount was calculated.

[0110] Table 2 Kinetic study data

[0111]

[0112]

[0113] Figure 4 It is the fitting of the pseudo-first-order kinetic and pseudo-second-order kinetic models of the phosphorus removal adsorbent prepared in Example 1; Figure 5 It is the fitting of the pseudo-first-order kinetic and pseudo-second-order kinetic models of the dephosphorization adsorbent prepared in Example 1. The adsorption of phosphate basically reaches equilibrium after 24 hours under the temperature changes of 298K, 303K, 308K and 313K.

[0114] From Table 2, we can see that the correlation coefficient R of the pseudo-second-order kinetic model 2 Both are higher than the R of the pseudo-first-order kinetic model. 2 In addition, the adsorption capacity Qe obtained by the pseudo-second-order kinetic model is more consistent with the experimental value Qe. The correlation coefficient R of the pseudo-second-order kinetic model of phosphate adsorption by the phosphorus removal adsorbent prepared in Comparative Example 1 2 are higher than the R of the pseudo-first-order kinetic model. 2 , and the adsorption capacity Qe obtained by the pseudo-second-order kinetic model is consistent with the experimental value Qe, but both are significantly lower than the adsorption capacity of the dephosphorus adsorbent prepared in Example 1. These results show that the pseudo-second-order kinetic model can better describe the kinetic data, and furthermore, it is obtained that the adsorption behavior occurring on the surface of the dephosphorus adsorbent is chemical adsorption, and the surface coating of Fe-BTC on the heat-treated acid-activated aluminum sludge-based material can significantly increase the adsorption capacity of the adsorbent material.

[0115] Experimental Example 5

[0116] The surface morphology of the dephosphorization adsorbent prepared in Example 1 before and after phosphate adsorption was observed using a scanning electron microscope.

[0117] Figure 6 This is a SEM image of the phosphorus removal adsorbent prepared in Example 1 before and after phosphate adsorption. As shown in the figure, the surface of the phosphorus removal adsorbent presents granular Fe-BTC wrapped in larger flat particles, which are stacked together in a disordered manner to form clusters. It can be seen that the prepared Fe-BTC material is an aggregate of many small nanocrystals with a particle size between 50-80nm, indicating the successful preparation of the phosphorus removal adsorbent. The surface of the material after phosphate adsorption becomes rougher due to the attachment of pollutants, and the pore size is significantly reduced, which proves the adsorption and clogging of pollutants. It can be seen that the structure and basic morphology of the material before and after adsorption have undergone some significant changes, and phosphate has been successfully adsorbed.

[0118] Experimental Example 6

[0119] This experimental example is to study the adsorption-desorption cycle experiment.

[0120] The dephosphorization adsorbent prepared in Example 1 was regenerated by ethanol immersion and desorption: the dephosphorization adsorbent after 24 hours of adsorption was immersed in anhydrous ethanol for 24 hours, and the ethanol solution was replaced 3 times in the middle. It was then washed with deionized water and dried in a forced air drying oven at 60°C. The regeneration adsorption experiment was repeated to test the adsorption capacity of the dephosphorization adsorbent after 5 adsorption and regeneration cycles.

[0121] Figure 6 It is a graph of the adsorption amount of the phosphorus removal adsorbent prepared in Example 1 in 5 adsorption and regeneration cycles; after 5 adsorption and regeneration cycles, the adsorption effect of the phosphorus removal adsorbent prepared in Example 1 is significantly reduced, but the adsorption amount can still be maintained at 20 mg P / g, indicating that the phosphorus removal adsorbent proposed in the present invention has a certain degree of reusability.

[0122] Experimental Example 7

[0123] The purpose of this experimental example is to design and determine the metal ion dissolution experiment.

[0124] 0.1 g of the dephosphorization adsorbent prepared in Example 1 and Comparative Example 1 was dispersed in 50 mL of distilled water and shaken for 24 h, and two parallel samples (50 mL) were taken for Al 3+ , Fe 3+ The metal ion concentration was determined to evaluate the metal dissolution concentration (mg / L) of the material. The test results are shown in Table 3.

[0125] Table 3 Metal ion dissolution concentration test results

[0126]

[0127] Table 3 shows the results of metal ion dissolution concentration test. In the solution of the dephosphorization adsorbent prepared in Example 1 after adsorption for 24 hours, the average concentration of dissolved Al element is 0.12 mg / L, while the concentration of dissolved Fe ions is only 0.0142 mg / L, both lower than that of Comparative Example 1. This shows that Fe-BTC is well coated on the surface, and the ion dissolution concentration is lower than that of Comparative Example 1, indicating that the dephosphorization adsorbent proposed by the present invention is an excellent adsorbent for phosphate and has good dissolution of main metal ions, and the material has safety for practical application.

[0128] The phosphorus removal adsorbent prepared in Examples 1-4 of the present invention modifies aluminum sludge by combining heat treatment and acid activation, effectively increasing its specific surface area and the number of surface active sites, and enhancing its adsorption capacity for phosphate. 3 6H 2 O The porous MOFs material of Fe-BTC is grown on the surface of the heat-treated acid-activated aluminum sludge-based material to achieve the coating of the aluminum sludge material, and further increase the specific surface area of ​​the adsorbent, optimize the structure of the composite adsorbent, and make it have higher chemical stability and adsorption efficiency. The dephosphorus adsorbent of the present invention can still maintain a high adsorption effect after repeated use, and the metal dissolution rate is low, avoiding the problem of secondary pollution, showing good environmental friendliness and sustainability. The preparation process of the present invention is simple to operate, mild conditions, no need to use complex equipment, has low cost, and is suitable for large-scale production and application. The method proposed by the present invention makes full use of aluminum sludge, a by-product of water plants, which not only realizes the resource utilization of waste, but also provides a new idea for solving the problem of eutrophication of water bodies, and realizes the strategy of "treating waste with waste and turning waste into treasure", and has broad application prospects.

[0129] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent, characterized in that: It is made by the following steps: 1) firstly heat-treating the original aluminum sludge without any treatment, and then cooling it to room temperature to obtain heat-treated aluminum sludge; 2) then subjecting the heat-treated aluminum sludge to acid activation treatment with an inorganic acid solution, washing to neutrality after the treatment, and drying to obtain a heat-treated acid-activated aluminum sludge-based material; 3) mixing the organic ligand and the inorganic base solution evenly and setting the mixture as solution 1 for later use; 4) FeCl3·6H2O and the heat-treated acid-activated aluminum sludge-based material obtained in step 2) are uniformly mixed in water to prepare a solution 2 for later use; 5) adding the solution 2 prepared in step 4) dropwise into the solution 1 prepared in step 3) at room temperature, and stirring continuously, collecting the precipitate, washing and drying to obtain the dephosphorus adsorbent.

2. The phosphorus removal adsorbent according to claim 1, characterized in that: The heat treatment temperature in step 1) is 300-800° C. and the heat treatment time is 0.5-4 h.

3. The phosphorus removal adsorbent according to claim 1, characterized in that: In step 2), the weight-to-volume ratio of the heat-treated aluminum sludge to the inorganic acid solution is 1:1-6 (g / ml).

4. The phosphorus removal adsorbent according to claim 3, characterized in that: Step 2) The inorganic acid solution is a hydrochloric acid solution or a sulfuric acid solution, the concentration of the hydrochloric acid solution is 0.5-6 mol / L, and the concentration of the sulfuric acid solution is 0.5-3 mol / L.

5. The phosphorus removal adsorbent according to claim 1, characterized in that: The molar ratio of the organic ligand to the inorganic base solution in step 3) is 1:2-4.

6. The phosphorus removal adsorbent according to claim 5, characterized in that: The organic ligand is trimesic acid, terephthalic acid, isophthalic acid or biphenyl dicarboxylic acid; the inorganic alkali solution is sodium hydroxide solution or potassium hydroxide solution.

7. The phosphorus removal adsorbent according to claim 1, characterized in that: The weight ratio of FeCl3·6H2O to the heat-treated acid-activated aluminum sludge-based material in step 4) is 1:0.2-1.

8. The phosphorus removal adsorbent according to claim 1, characterized in that: In step 5), the amounts of solution 1 and solution 2 are prepared so that the molar ratio of the organic ligand to FeCl3·6H2O is 1:1-2.

9. A method for preparing the Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent according to any one of claims 1 to 8, characterized in that: It includes the following steps: 1) firstly heat-treating the original aluminum sludge without any treatment, and then cooling it to room temperature to obtain the heat-treated aluminum sludge; 2) then subjecting the heat-treated aluminum sludge to acid activation treatment with an inorganic acid solution, washing to neutrality after the treatment, and drying to obtain a heat-treated acid-activated aluminum sludge-based material; 3) mixing the organic ligand and the inorganic base solution evenly and setting the mixture as solution 1 for later use; 4) FeCl3·6H2O and the heat-treated acid-activated aluminum sludge-based material obtained in step 2) are uniformly mixed in water to prepare a solution 2 for later use; 5) adding the solution 2 prepared in step 4) dropwise into the solution 1 prepared in step 3) at room temperature, and continuously stirring, collecting the precipitate, washing and drying it to obtain a dephosphorus adsorbent.

10. Use of the Fe-BTC coated aluminum sludge-based phosphorus removal adsorbent as described in any one of claims 1 to 8 as a water resource for treating eutrophication of water bodies.

Citation Information

Patent Citations

  • Granular adsorbent capable of efficiently removing phosphorus in waste water and preparation and application method of granular adsorbent

    CN107159097A

  • Straw loaded MOF material adsorbent and preparation method and application thereof

    CN111229171A

  • Preparation method and application of activated aluminum oxide loaded Fe-MOF green composite granules

    CN112774635A